Comparison of vascular access outcomes in patients with end-stage renal disease attributed to systemic lupus erythematosus vs. other causes: a retrospective cohort study. Issue 1 (December 2016) - Plantinga, Laura; Lim, S.; Patzer, Rachel; Pastan, Stephen; Drenkard, Cristina
Abstract Background U.S. hemodialysis patients with systemic lupus erythematosus (SLE) and end-stage renal disease (ESRD) are less likely than other ESRD patients to have a permanent vascular access (fistula or graft) in place at the dialysis start. We examined whether vascular access outcomes after dialysis start differed for SLE vs. other ESRD patients. Methods Among U.S. patients initiating hemodialysis in 2010 with only a catheter (n = 40, 911; 384 with SLE) and using a permanent access on first dialysis (n = 13, 073; 48 with SLE), we examined the association of SLE status with time to first placement of a permanent access (among catheter-only patients) and to loss of access patency (among patients using a permanent access on first dialysis), both censored 1 year after dialysis start, using multivariable Cox proportional hazards models. Results Among catheter-only patients, 46.1 % vs. 54.5 % of those with SLE-ESRD vs. other ESRD had a permanent access placed within 1 year after dialysis start. However, with adjustment, there was no association of 1-year placement with SLE status [HR = 1.00 (95 % CI, 0.86-1.17)]. SLE-ESRD vs. other ESRD patients starting dialysis with a permanent access were less likely to experience a 1-year loss of patency (43.8 % vs. 55.0 %), but this association was not statistically significant after adjustment [HR = 0.88 (0.57-1.37)]. Conclusion These results suggest that SLE-ESRD patients starting dialysis with a catheter are not more likely to have a permanent access placed in the first year of dialysis, despite an observed lack of association of SLE status with subsequent loss of vascular access patency among those starting dialysis with a permanent access.